Trapping Cultures For Arbuscula Mycorrhyz Fungi (AMF) Spores Traping From Post-Mine Asphalt Soils Using Different Host Plants - Tuheteru, Faisal Danu; Husna; Asrianti Arif; Albasri; Rahmat; Wiwin Rahmawati Nurdin (Asosiasi Mikoriza Indonesia, 2024)
Spore trapping Culture has the advantage of producing AMF. inoculum production and higher A.M.F. colonization efficiency. This research aims to determine suitable hostnames for AMF trapping. This research was conducted at the Plastic House of the Indonesian Mycorrhizal Association (AMI.) Southeast Sulawesi Branch, UHO Old Campus, and the UHO. Forestry and Environmental Science Laboratory Unit lasted 3 months from May – June 2023. This research used a factorial, completely randomized design method with two factors: the first factor is a type of location, including L10 LM10, and the second factor is the type of host plant, including Pueraria javanica and Sorhum bicolar. The results showed that the interaction of the host plant and location had no significant effect on the number of spores and AMF colonization. Pueraria Javanica significantly increased the number of spores for both L10 and LM10, with an average number of spores of 84. Seven dominant types of A.M.F. from the Glomeraceae family were found